The histone methylation readers MRG1/MRG2 and the histone chaperones NRP1/NRP2 associate in fine‐tuning Arabidopsis flowering time. (12th May 2020) - An, Zengxuan; Yin, Liufan; Liu, Yuhao; Peng, Maolin; Shen, Wen‐Hui; Dong, Aiwu
Summary: Histones are highly basic proteins involved in packaging DNA into chromatin, and histone modifications are fundamental in epigenetic regulation in eukaryotes. Among the numerous chromatin modifiers identified in Arabidopsis ( Arabidopsis thaliana ), MORF‐RELATED GENE (MRG)1 and MRG2 have redundant functions in reading histone H3 lysine 36 trimethylation (H3K36me3). Here, we show that MRG2 binds histone chaperones belonging to the NUCLEOSOME ASSEMBLY PROTEIN 1 (NAP1) family, including NAP1‐RELATED PROTEIN (NRP)1 and NRP2. Characterization of the loss‐of‐function mutants mrg1 mrg2, nrp1 nrp2 and mrg1 mrg2 nrp1 nrp2 revealed that MRG1/MRG2 and NRP1/NRP2 regulate flowering time through fine‐tuning transcription of floral genes by distinct molecular mechanisms. In particular, the physical interaction between NRP1/NRP2 and MRG1/MRG2 inhibited the binding of MRG1/MRG2 to the transcription factor CONSTANS (CO), leading to a transcriptional repression of FLOWERING LOCUS T ( FT ) through impeded H4K5 acetylation (H4K5ac) within the FT chromatin. By contrast, NRP1/NRP2 and MRG1/MRG2 act together, likely in a multiprotein complex manner, in promoting the transcription of FLOWERING LOCUS C ( FLC ) via an increase of both H4K5ac and H3K9ac in the FLC chromatin. Because the expression pattern of FLC represents the major category of differentially expressed genes identified by genome‐wide RNA‐sequencing analysis in the mrg1 mrg2, nrp1 nrp2 and mrg1 mrg2 nrp1 nrp2 mutants, it is reasonable to speculate that the NRP1/NRP2‐MRG1/MRG2 complex may be involved in transcriptional activation of genes beyond FLC and flowering time control. Significance Statement: The identification of a physical interaction between the H3K36me3‐reader MORF‐RELATED GENE (MRG)1/MRG2 and the histone‐chaperone NAP1‐RELATED PROTEIN (NRP)1/NRP2 is significant. This interaction inhibits MRG1/MRG2 to bind CONSTANS in FLOWERING LOCUS T transcription, whereas MRG1/MRG2 and NRP1/NRP2 cooperate in a multiprotein complex manner in promoting FLOWERING LOCUS C ( FLC ) transcription via elevation of both H4K5ac and H3K9ac in the FLC chromatin.